Phylogenetics : theory and practice of phylogenetic systematics - Wiley, E. O.; Lieberman, Bruce S. (Hoboken, N.J. : Wiley-Blackwell, 2011)
'This new edition of Phylogenetics captures the very essence of this rapidly evolving discipline. Written for the practicing systematist and phylogeneticist, it addresses both the philosophical and technical issues of the field, as well as surveys general practices in taxonomy. Major sections of the book deal with the nature of species and higher taxa, homology and characters, trees and tree graphs, and biogeography -- the purpose being to develop biologically relevant species, character, tree, and biogeographic concepts that can be applied fruitfully to phylogenetics. The book then turns its focus to phylogenetic trees, including an in-depth guide to tree-building algorithms. Additional coverage includes: Parsimony and parsimony analysis -- Parametric phylogenetics including maximum likelihood and Bayesian approaches -- Phylogenetic classification -- Critiques of evolutionary taxonomy, phenetics, and transformed cladistics -- Specimen selection, field collecting, and curating -- Systematic publication and the rules of nomenclature. Providing a thorough synthesis of the field, this important update to Phylogenetics is essential for students and researchers in the areas of evolutionary biology, molecular evolution, genetics and evolutionary genetics, paleontology, physical anthropology, and zoology.'--Provided by publisher.
Introduction -- Species and Speciation -- Supraspecific Taxa -- Tree Graphs -- Characters and Homology -- Parsimony and Parsimony Analysis -- Parametric Phylogenetics -- Phylogenetic Classification -- Historical Biogeography -- Specimens and Curation -- Publication and Rules of Nomenclature -- Literature Cited -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Phylogeny; Biology -- Classification; Cladistic analysis; Biology -- Classification; Science; Natural history; SCIENCE -- Life Sciences -- Evolution; Biology; Cladistic analysis; Phylogeny; Electronic books; Classification